Aplikasi Wolbachia Sebagai Kontrol Biologi Demam Berdarah Dengue : Kajian Literatur - Fadly Hidayaturochman; Aghniya Nur Rizka Fadila; Haryanto Haryanto (Jurnal Biodiversitas dan Bioteknologi, 2024)
Dengue fever is a disease transmitted by the Aedes aegypti mosquito. The infection rate in Indonesia in 2023 reached 42,690 people and 317 people died. In fact, Indonesia has one of the highest rates among other Southeast Asian countries. The use of insecticides in handling these cases causes mosquito resistance and air pollution. One of the efforts in controlling Dengue transmission can be done by biological control with the use of endosymbionts, namely Wolbachia. Therefore, the purpose of this literature review is to determine the preparation of Wolbachia-infected mosquitoes and their effectiveness as biological control of DHF, as well as the mechanism of Wolbachia mosquitoes in controlling DHF. The method of writing this literature review used online literature searches sourced from Google Scholar, Pubmed and Science Direct. Wolbachiainfected Aedes aegypti mosquitoes were prepared by confirming positive Wolbachia-infected mosquitoes using the PCR method, and then cultured in the laboratory. Mosquito eggs from matings are sorted manually, then Wolbachia bacteria are injected into the eggs using an automated microinjector, Wolbachiainfected mosquito larvae are bred, and quality control is conducted prior to release. Wolbachia mosquito technology has been proven to reduce Dengue infection by 77.1% and prevent hospitalization by 83% in Yogyakarta City.